Distinguished Doctor: Lines to His Image - Mizrahi, Solly (Technium Education and Humanities, 2022)
ABSTRACT: It takes many years to become recognized as a distinguished physician. During the long maturing period a large collection of innate and acquired qualities are being conglomerated to assemble a unique personality. Herein we study the appropriate characteristics that a respected clinician should always cherish.